Underlying Challenges for Russian Venture Industry Development and Methods for Their Solution - A. M. Margolin; L. P. Sinyutin (Управленческое консультирование)
The authors of this article set a goal to identify the most relevant obstacles for venture capital development in Russia. In order to achieve this goal, statistical analysis was carried out as well as valuation of different quantitative and qualitative information, including primary sources (interviews with venture industry experts) was conducted. Russian and foreign literature was exploited during this research. The analysis of the Russian venture capital development dynamics was carried out, as well as the major regulatory aspects of the industry were examined. Based on the results of the research, certain recommendations were provided, which, according to the authors, are capable of supporting venture investments in the long term and accelerating the volume growth of capital raising by domestic startups.